Pengaruh Struktur Modal Dan Profitabilitas terhadap Nilai Perusahaan agar mampu bersaing dan berkembang secara berkelanjutan - Nyayu Khairani Putri; Dian Septianti; Sasiska Rani (Fakultas Ekonomi Universitas Tridinanti Palembang, 2024)
Abstract : This study aims to find out how government-owned banks listed on the Indonesia Stock Exchange can increase their value. The researchers examine whether the amount of debt and the bank's profitability affect the bank's value. The study focuses on two important factors: the